The case of the cosmic kidnapping - Dixon, Franklin W.; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books ; Simon & Schuster, 1993)
When Chet's boss seems to vanish without a trace, the Hardys suspect a UFO hoax.
"A Minstrel book."
At head of title: The Hardy boys.
Keywords: Mystery fiction; Young adult fiction